Magnetic interactions in a series of homodinuclear lanthanide complexes - Comba, Peter; Großhauser, Michael; Klingeler, Rüdiger; Koo, Changhyun; Lan, Yanhua; Müller, Dennis; Park, Jaena; Powell, Annie; Riley, Mark J.; Wadepohl, Hubert (Inorganic chemistry, 2015)
A series of seven isostructural homodinuclear lanthanide complexes are reported. The magnetic properties (ac and dc SQUID measurements) are discussed on the basis of the X-ray structural properties which show that the two lanthanide sites are structurally different. MCD spectroscopy of the dysprosium(III) and neodymium(III) complexes ([DyIII2(L)(OAc)4]+ and [NdIII2(L)(OAc)4]+) allowed us to thoroughly analyze the ligand field, and high-frequency EPR spectroscopy of the gadolinium(III) species ([GdIII2(L)(OAc)4]+) showed the importance of dipolar coupling in these systems. An extensive quantum-chemical analysis of the dysprosium(III) complex ([DyIII2(L)(OAc)4]+), involving an ab initio (CASSCF) wave function, explicit spin-orbit coupling (RASSI-SO), and a ligand field analysis (Lines model and Stevens operators), is in full agreement with all experimental data (SQUID, HF-EPR, MCD) and specifically allowed us to accurately simulate the experimental χT versus T data, which therefore allowed us to establish a qualitative model for all relaxation pathways.
Gesehen am 02.12.2020